2001
DOI: 10.1016/s0304-3959(00)00415-2
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the fusimotor-muscle spindle system from chemosensitive nerve endings in cervical facet joints in the cat: possible implications for whiplash induced disorders

Abstract: The aim of the present study was to establish if there exists reflex connections from ligamentous structures in cervical facet joints and the fusimotor system of dorsal neck muscles. In seven cats, anaesthetized with alpha-chloralose, bradykinin (BK) of concentrations between 12 and 50 microg was injected into the facet joint between C1 and C2. Recordings were made from single muscle spindle afferents (MSA) originating in contralateral trapezius and splenius muscles (TrSp). Fusimotor induced changes in the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 43 publications
1
51
1
2
Order By: Relevance
“…In particular, facet joint pain has been shown to activate γ motor neurons and thereby increase the sensitivity of muscle spindles [35][36][37]. In addition, numerous studies have demonstrated that spinal manipulation increases the afferent discharge from mechanoreceptors and subsequently quiets α motor neurons, resulting in reduced EMG activity of paraspinal muscles [38].…”
Section: The Physiology Of Pain Related To Myofascial Trigger Pointsmentioning
confidence: 99%
“…In particular, facet joint pain has been shown to activate γ motor neurons and thereby increase the sensitivity of muscle spindles [35][36][37]. In addition, numerous studies have demonstrated that spinal manipulation increases the afferent discharge from mechanoreceptors and subsequently quiets α motor neurons, resulting in reduced EMG activity of paraspinal muscles [38].…”
Section: The Physiology Of Pain Related To Myofascial Trigger Pointsmentioning
confidence: 99%
“…18,82 After traumatic neck injury, disturbances in sensorimotor control, primarily via altered cervical input, may occur due to a combination of factors. Apart from direct trauma, factors associated with the trauma, such as inflammation, 110 functional impairment, 32 morphological changes to musculature, 29 pain, 66 and psychological distress, 79 may alter cervical input or CNS representation. This can influence cervical reflex connections to the visual and vestibular systems and result in subsequent secondary disturbances.…”
mentioning
confidence: 99%
“…lactic acid, arachidonic acid, bradykinin and serotonin) [36,37]. Moreover, bradykinin injection into cervical facet joints [38] as well as the temporomandibular joint [39] was shown to affect the stretch sensitivity of the neck muscle spindles. Evidence suggests that the acuity of proprioceptive information from muscle spindle afferents can be impaired by fatigue, inflammation as well as trauma [35].…”
Section: Effects Of the The Sensorimotor Systemmentioning
confidence: 99%